Fabrication of Nanostructured Cadmium Selenide Thin Films for Optoelectronics Applications - Hussain, Shahnwaz; Iqbal, Mazhar; Khan, Ayaz Arif; Khan, Muhammad Nasir; Mehboob, Ghazanfar; Ajmal, Sohaib; Ashfaq, J. M.; Mehboob, Gohar; Ahmed, M. Shafiq; Khisro, Said Nasir; Li, Chang-Jiu; Chikwenze, Raphael; et al. (Frontiers in Chemistry, 2021)
There is lot of research work at enhancing the performance of energy conversion and energy storage devices such as solar cells, supercapacitors, and batteries. In this regard, the low bandgap and a high absorption coefficient of CdSe thin films in the visible region, as well as, the low electrical resistivity make them ideal for the next generation of chalcogenide-based photovoltaic and electrochemical energy storage devices. Here, we present the properties of CdSe thin films synthesized at temperatures (below 100°C using readily available precursors) that are reproducible, efficient and economical. The samples were characterized using XRD, FTIR, RBS, UV-vis spectroscopy. Annealed samples showed crystalline cubic structure along (111) preferential direction with the grain size of the nanostructures increasing from 2.23 to 4.13 nm with increasing annealing temperatures. The optical properties of the samples indicate a small shift in the bandgap energy, from 2.20 to 2.12 eV with a decreasing deposition temperature. The band gap is suitably located in the visible solar energy region, which make these CdSe thin films ideal for solar energy harvesting. It also has potential to be used in electrochemical energy storage applications.